Audyt wewnętrzny jako narzędzie badania procesów gospodarczych przedsiębiorstwa - Mytlewski, Adam (Internal Audit as a Process Research Tool, 2009)
The article shows the role of internal audit in business processes as a tool to review compliance with internal and external regulations. In the current environment, internal audit has to bring true added value for an organization, such as identifying potential areas for reducing undesired or unanticipated costs arising from ineffective risk management and reducing losses caused by low-quality project management, improper processes and inaccurate management information for decision making. Internal audit has to be much closer to management and has to become more involved in operating decision making. Internal audit, in co-operation with the management of the company, should continuously monitor and measure the exposure to risks, helping to ensure that they are appropriately managed. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 178-182